Revealing Stereotypes: Evidence from Immigrants in Schools - Alesina, Alberto; Carlana, Michela; La Ferrara, Eliana; Pinotti, Paolo (American Economic Review, 2024)
We study how people change their behavior after being made aware of bias. Teachers in Italian schools give lower grades to immigrant students relative to natives of comparable ability. In two experiments, we reveal to teachers their own stereotypes, measured by an Implicit Association Test (IAT). In the first, we find that learning one’s IAT before assigning grades reduces the native-immigrant grade gap. In the second, IAT disclosure and generic debiasing have similar average effects, but there is heterogeneity: teachers with stronger negative stereotypes do not respond to generic debiasing but change their behavior when informed about their own IAT. (JEL D91, I24, J15, J45)